2022
DOI: 10.1038/s41598-022-12687-3
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoflowers encapsulated in thermosensitive fluorescent liposomes for hyperthermia treatment of lung adenocarcinoma

Abstract: Magnetic hyperthermia (MHT) is in the spotlight of nanomedical research for the treatment of cancer employing magnetic iron oxide nanoparticles and their intrinsic capability for heat dissipation under an alternating magnetic field (AMF). Herein we focus on the synthesis of iron oxide nanoflowers (Nfs) of different sizes (15 and 35 nm) and coatings (bare, citrate, and Rhodamine B) while comparing their physicochemical and magnetothermal properties. We encapsulated colloidally stable citrate coated Nfs, of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 69 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…It is of major importance that nanoparticles aiming to serve as theranostic agents have minimal interactions with blood components so as not to compromise their systemic administration. To this end, nanosystems such as iron oxide or gold nanoparticles must prove their biocompatibility before being intravenously injected into a living organism [ 61 , 62 ]. In our case, all samples exhibited minimal hemoglobin release from the RBCs, indicating negligible hemolysis according to the <10% acceptance limit for biopharmaceuticals [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is of major importance that nanoparticles aiming to serve as theranostic agents have minimal interactions with blood components so as not to compromise their systemic administration. To this end, nanosystems such as iron oxide or gold nanoparticles must prove their biocompatibility before being intravenously injected into a living organism [ 61 , 62 ]. In our case, all samples exhibited minimal hemoglobin release from the RBCs, indicating negligible hemolysis according to the <10% acceptance limit for biopharmaceuticals [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers also found that the proliferation of lung cancer cells was slowed by SPIONs coated with silica monolayers, as shown in Table 3 [ 315 ]. In another study, researchers discovered that iron oxide nanoflowers loaded in thermo-sensitive fluorescent liposomes could enhance the efficacy of cytotoxic drugs against lung cancer by causing hypothermia [ 316 ].…”
Section: Novel Nanocarriers Based Treatment Approachmentioning
confidence: 99%
“…75 Alternatively, the encapsulation of magnetic NPs into liposomes, both produced synthetically or by magnetotactic bacteria, results also in a potential strategy for enhanced therapeutic heating. [76][77][78] Nevertheless, it is important to note that the establishment of dipolar interactions between iron oxide NPs can have positive but also negative effects on the heating performance depending on several parameters. 79,80…”
Section: Surface Coatingmentioning
confidence: 99%